2023
DOI: 10.1371/journal.pgph.0000688
|View full text |Cite
|
Sign up to set email alerts
|

A multi-level analysis of prevalence and factors associated with caesarean section in Nigeria

Abstract: The choice of caesarean section (CS) plays a significant role in maternal and neonatal health. However, suboptimal CS uptake suggests unmet obstetric care leading to adverse maternal and neonatal health. Considering that maternal health problems in Nigeria remain a public health problem, this present study aims to assess the prevalence and multilevel factors associated with caesarean section among women of reproductive age in Nigeria. Data from the 2018 Nigeria Demographic and Health Survey were analysed. Our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
1
3
0
Order By: Relevance
“…Participants who struggled emotionally were among those who were compelled to have a caesarian section and who felt disappointed, referencing cultural and religious beliefs. This aligns with a previous study in Nigeria that identified religious beliefs as a strong factor influencing cesarean section uptake [15].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Participants who struggled emotionally were among those who were compelled to have a caesarian section and who felt disappointed, referencing cultural and religious beliefs. This aligns with a previous study in Nigeria that identified religious beliefs as a strong factor influencing cesarean section uptake [15].…”
Section: Discussionsupporting
confidence: 92%
“…Nigeria, situated in sub-Saharan Africa, has not been immune to this global surge in caesarean section rates [2,15]. In Nigeria, there has been minimal fluctuation over the years in the proportion of births delivered via caesarean section, hovering at around 3% (3% in 1990, 2% in 2008, 3% in 2018, and 3.7% in 2021) [16,17].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations